2011
DOI: 10.1002/ibd.21322
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-gamma (PPAR-γ) expression is downregulated in patients with active ulcerative colitis

Abstract: FIGURE 1. Gene expression of PPAR-c in rectal mucosa from patients with UC (active/remission) and the constitutive gene RPL0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 3 publications
6
26
1
2
Order By: Relevance
“…These findings demonstrated that deregulation of PPAR-γ may play an important role in the pathogenic process of UC. The present data were also consistent with the results obtained by Yamamoto-Furusho et al (25), which indicated that the mRNA expression of PPAR-γ was decreased in rectal mucosa from patients with active UC compared with UC patients in remission, and PPAR-γ gene expression was negatively correlated with endoscopic activity, as determined by Spearman correlation test. The present study did not identify a correlation between the expression of PPAR-γ and the site of UC lesions, which indicates that PPAR-γ was involved in an alternative component of the UC intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…These findings demonstrated that deregulation of PPAR-γ may play an important role in the pathogenic process of UC. The present data were also consistent with the results obtained by Yamamoto-Furusho et al (25), which indicated that the mRNA expression of PPAR-γ was decreased in rectal mucosa from patients with active UC compared with UC patients in remission, and PPAR-γ gene expression was negatively correlated with endoscopic activity, as determined by Spearman correlation test. The present study did not identify a correlation between the expression of PPAR-γ and the site of UC lesions, which indicates that PPAR-γ was involved in an alternative component of the UC intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…The levels of both metalloproteinase-2 and metalloproteinase-9 were markedly increased after incubation of HCT116 cells with triptolide. A previous study demonstrated that active PPARγ caused the inhibition of alimentary canal inflammation; thus, its expression is of significance for the treatment of colon cancer [26]. Our study demonstrated that triptolide treatment of AOM/DSS mice significantly prevented colon tissue inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…12 In addition to the biliary epithelial cells of PBC, a reduction of PPARγ expression in the colonic epithelial mucosa is reportedly associated with the pathogenesis of inflammatory bowel diseases (IBD). [13][14][15][16] Furthermore, the expression of PPARγ is affected by the commensal intestinal flora and ligands (agonists) for PPARγ can attenuate colitis in IBD-model mice, supporting the notion that PPARγ ligands may have salutary effects on IBD. 14,[16][17][18] As for anti-inflammatory activities, the activation of PPARγ by its ligands is shown to inhibit the expression of pro-inflammatory cytokines, the induction of which is mediated via NF-κB and mitogen activated protein kinase (MAPK).…”
Section: Introductionmentioning
confidence: 81%